Skin-associated Corynebacterium amycolatum shares cobamides - M. H. Swaney; N. Henriquez; T. Campbell; J. Handelsman; L. R. Kalan (mSphere)
ABSTRACT The underlying interactions that occur to maintain skin microbiome composition, function, and overall skin health are largely unknown. Often, these types of interactions are mediated by microbial metabolites. Cobamides, the vitamin B12 family of cofactors, are essential for metabolism in many bacteria but are only synthesized by a fraction of prokaryotes, including certain skin-associated species. Therefore, we hypothesize that cobamide sharing mediates skin community dynamics. Preliminary work predicts that several skin-associated Corynebacterium species encode de novo cobamide biosynthesis and that their abundance is associated with skin microbiome diversity. Here, we show that commensal Corynebacterium amycolatum produces cobamides and that this synthesis can be tuned by cobalt limitation. To demonstrate cobamide sharing by C. amycolatum, we employed a co-culture assay using an E. coli cobamide auxotroph and showed that C. amycolatum produces sufficient cobamides to support Escherichia coli growth, both in liquid co-culture and when separated spatially on solid medium. We also generated a C. amycolatum non-cobamide-producing strain (cob–) using UV mutagenesis that contains mutated cobamide biosynthesis genes cobK (precorrin-6X reductase) and cobO (corrinoid adenosyltransferase) and confirm that disruption of cobamide biosynthesis abolishes the support of E. coli growth through cobamide sharing. Our study provides a unique model to study metabolite sharing by microorganisms, which will be critical for understanding the fundamental interactions that occur within complex microbiomes and for developing approaches to target the human microbiota for health advances.IMPORTANCEThe human skin serves as a crucial barrier for the body and hosts a diverse community of microbes known as the skin microbiome. The interactions that occur to maintain a healthy skin microbiome are largely unknown but are thought to be driven in part, by nutrient sharing between species in close association. Here we show that the skin-associated bacteria Corynebacterium amycolatum produces and shares cobalamin, a cofactor essential for survival in organisms across all domains of life. This study provides a unique model to study metabolite sharing by skin microorganisms, which will be critical for understanding the fundamental interactions that occur within the skin microbiome and for developing therapeutic approaches aiming to engineer and manipulate the skin microbiota.